Permanent education in nursing care in the maintenance of the central venous catheter of peripheral insertion - Silva, Klebson Rodrigues da; Neves, Lais Gabriela da Silva; Silva, Luciane Fayal da; Silva, Marcos José Risuenho Brito; Simor, Alzinei (Revista de Enfermagem da UFPI, 2022)
Objective: To report a continuing education activity on the maintenance of PICC developed by nurses and nursing students in an oncology hospital. Methods: This is a study of the type of experience report based on Problematization following the five stages of the Maguerez Arch. In the observation, the use of PICC was verified in the hospital therapy protocol, and the complexity of its use was considered, focusing on the need for updating on care. For the theorization, a literature review was performed. In the fourth stage, a permanent education was defined as an approach with professionals. The activity occurred with the realization of a Quiz and explanation of the content with the didactic material produced. Results: Quiz questions and material targeted activity. The team demonstrated to know the answers, and it was up to the mediator to complement the subject. The activity has given way to the standardization of catheter procedures and care, in addition to the sharing of experience among professionals. Conclusion: In the use of PICC, improving care promotes the prevention of complications and effective care. The continuity of developing the theme is necessary, because the improvement of the professional needs to be continuous.